2014
DOI: 10.1371/journal.pbio.1002004
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Correlation Mechanisms and Their Role in Feature Selection: A Single-Unit Study in Primate Somatosensory Cortex

Abstract: How neurons pay attention Top-down selective attention mediates feature selection by reducing the noise correlations in neural populations and enhancing the synchronized activity across subpopulations that encode the relevant features of sensory stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…1A). The single-unit data for this study have previously been used in other studies that addressed the link between firing rate and behavior after the motion pulse occurred Farah et al, 2014). Here we instead focused on the period leading up to the motion pulse.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1A). The single-unit data for this study have previously been used in other studies that addressed the link between firing rate and behavior after the motion pulse occurred Farah et al, 2014). Here we instead focused on the period leading up to the motion pulse.…”
Section: Resultsmentioning
confidence: 99%
“…Behavioral task. The data for this study have been previously described Farah et al, 2014). Two male monkeys (Macaca mulatta) were trained to perform a coherent motion pulse detection task outlined in Figure 1C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Attending to the tactile information of a bimodal visuo-tactile stimulus increased the firing rates of neurons in the primary (SI) and secondary (SII) somatosensory cortices as compared to the case when attention was directed to the visual information (Hsiao, O'Shaughnessy, & Johnson, 1993). When attention had to be directed to one of two tactile features (orientation and vibratory frequency) higher firing rates were observed in SII neurons selective for this specific feature (Gomez-Ramirez, Trzcinski, Mihalas, Niebur, & Hsiao, 2014). Furthermore, it has been shown that tactile attention increased synchronization of neural spiking activity of feature selective cells in the SII, which correlated with performance (Gomez-Ramirez et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
“…All other points were assigned a zero value. We convolved MUA activity with an asymmetric Gaussian filter (30ms duration, with a rising slope = 19.91mV/s) to derive instantaneous MUA (Gomez-Ramirez et al, 2014). Individual observations used in the statistics comprised averaged activity between -1500ms and -500ms prior to the onset of the tactile stimulus.…”
Section: Analysesmentioning
confidence: 99%